(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Polycystic ovarian disease (PCOD) is a common endocrine disorder in reproductive-age women, often managed with conventional therapies that carry limitations. Ayurveda offers a holistic approach through Shodhana and Shamana interventions. To evaluate the effect of an Ayurvedic regimen combining Uttar Basti and Sanshamana Aushadhi in PCOD management. A 40-year-old female with PCOD, hypothyroidism, and secondary infertility, presenting with irregular cycles, hirsutism, acne and dysmenorrhea underwent a structured plan. This included Chitakadi Vati for 5 days, Rasnasaptakadi Niruha Basti and Sahacharadi Taila Anuvasana Basti on the 5th–6th day of the cycle, followed by Uttar Basti with Jatyadi Ghrita on the 7th–9th day for three consecutive cycles. Ovacare syrup and tablets were administered orally for three months. Outcomes were assessed clinically and with ultrasound. Significant improvements were noted: acne resolved, hirsutism reduced, hypomenorrhea improved, and menstrual cycles became regular. Ovarian volume reduced on ultrasound. The total symptoms score decreased from 9 to 4, with additional relief in dysmenorrhea, anxiety, and sleep disturbance. The integrative Ayurvedic protocol, especially Jatyadi Ghrita Uttar Basti, demonstrated promising results in PCOD management, suggesting a safe and holistic alternative requiring further validation.